The Effectiveness of Performance of E-Office System in Tanzania's Public Institutions - Kanyengele Abdallah, Sophia; A. Kopoka, Peter (Faculty of Social and Political Science Universitas Brawijaya, 2024)
The main objective of this study was to examine the effectiveness of the performance of the e-office system in Tanzania's Public Institutions at the President's Office of Public Service Management and Good Governance (POPSMGG). Specifically, the study determined the extent to which the e-office system is used at PO PSMGG, assessed the impact of using the e-office system at PO PSMGG, and examined the challenges faced in using the e-office system at PO PSMGG. The study adopted a cross-sectional research design. A total of 132 participants participated in this study, equal to an 86.8% response rate. The Resource-Based View theory guided the study. The study employed questionnaires and interview methods to collect data. The findings revealed that the majority of respondents, 58%, said they use e-office daily. The study results indicated that most respondents, 90%, agreed that the e-office system improves customer service. The findings revealed that most of the respondents, 71% disagreed with the statement that the lack of adequate ICT infrastructure affects the POPSMGG to use the e-office system. Also, the study revealed that most of the respondents, 59% disagreed with the statement that the most significant barrier to using the e-office system is a lack of willingness to use the system. Generally, the overall results regarding the challenges experienced when using the e-office system showed that most respondents indicated issues such as unreliable power supply, security concerns, and technology dependency. The study recommends that the government integrate the e-office system with other government systems to facilitate data and information sharing.